Laparoscopic cysto-gastrostomy for management of pancreatic pseudocyst. Single center experience in upper Egypt - Mohamed, Wael Barakaat Ahmed; Abdelmageed, Magdy Khalil; Gomaa, Emad (International Surgery Journal, 2017)
Background: One of the most common lumps of the pancreas is the pancreatic pseudocyst, with an estimated incidence of 70-80%. There are two main options for treatment pancreatic pseudocyst if it persists beyond six weeks and not respond to conservative treatment, surgical (laparoscopic and conventional open surgery) and non-surgical treatment (endoscopic and percutaneous drainage through ultrasonography or computed tomography guide). The objective of this study was to evaluate the outcome of laparoscopic pancreatic cystogastrostomy for pancreatic pseudocyst as regard operative and postoperative results in Sohag university Hospitals. Methods: This was a prospective observational single center study at the General surgery department Sohag University Hospitals, Egypt. The study populations were patients suffering from pancreatic pseudocyst attend to the outpatient clinic from March 2014 to March 2017. All patients were evaluated by history taking, physical examination, laboratory investigation and imaging evaluation by abdominal ultrasonography and contrast enhanced computed tomography of the abdomen. Results: Between March 2014 and March 2017, 14 patients with pancreatic pseudocyst had fulfilled our inclusion criteria and included in this study. 8 patients were female and 6 patients were male. 12 patients had previous history of acute biliary pancreatitis at least 6 months before the operation. 2 patient had undetermined pancreatitis. The mean age of the patient was 45.5±1.8 years and the mean operative time was 153±29 minutes the mean time to start oral fluid was 29±2 hours. 12 of the patient shad a laparoscopic cholecystectomy as all of them had acute biliary pancreatitis all operations were completed laparoscopically no conversion to open surgery was done.no mortality detected in our study .no intraoperative complications only one case had postoperative bleeding that respond to conservative therapy, one case of postoperative wound infection responds to antibiotic therapy. All cysts were resolved completely success rate (100%). The mean hospital stay was 4.35±0.28 days. The mean follows up time was 10.5±0.875 months. Conclusions: Laparoscopic cysogastrotomy is as safe, effective procedure for management of the pancreatic pseudocyst in the hand of expert well trained laparoscopic with enough equipment.